Immunohistochemical analyses of paraffin-embedded sections after primary surgery or trimodality treatment in esophageal carcinoma. (September 2022) - Igbo, Benjamin Terfa; Linge, Annett; Frosch, Susanne; Suckert, Theresa; Stolz-Kieslich, Liane; Löck, Steffen; Kumaravadivel, Mani Sankari; Welsch, Thilo; Weitz, Jürgen; Sommer, Ulrich; Aust, Daniela; Troost, Esther G.C.
Highlights: Changes in the tumor microenvironment of esophageal cancers, both in squamous cell carcinoma and adenocarcinoma, were found when comparing tumor resection specimen having undergone neoadjuvant radiochemotherapy followed by resection or resection only. Selected markers of the tumor microenvironment, i.e., Ki67, p53, CXCR4 and PD1 were found to be downregulated in hypoxic regions compared to normoxic regions. These findings will be correlated with microscopic tumor extension measurements in a subsequent, prospectively included cohort of esophageal cancer patients. Abstract: Background: The microscopic tumor extension before, during or after radiochemotherapy (RCHT) and its correlation with the tumor microenvironment (TME) are presently unknown. This information is, however, crucial in the era of image-guided, adaptive high-precision photon or particle therapy. Materials and methods: In this pilot study, we analyzed formalin-fixed paraffin-embedded (FFPE) tumor resection specimen from patients with histologically confirmed squamous cell carcinoma (SCC; n = 10) or adenocarcinoma (A; n = 10) of the esophagus, having undergone neoadjuvant radiochemotherapy followed by resection (NRCHT + R) or resection (R)]. FFPE tissue sections were analyzed by immunohistochemistry regarding tumor hypoxia (HIF-1α), proliferation (Ki67), immune status (PD1), cancer cell stemness (CXCR4), and p53 mutation status. Marker expression in HIF-1α subvolumes was part of a sub-analysis. Statistical analyses were performed using one-sided Mann-Whitney tests and Bland-Altman analysis. Results: In both SCC and AC patients, the overall percentages of positive tumor cells among the five TME markers, namely HIF-1α, Ki67, p53, CXCR4 and PD1 after NRCHT were lower than in the R cohort. However, only PD1 in SCC and Ki67 in AC showed significant association (Ki67: p = 0.03, PD1: p = 0.02). In the sub-analysis of hypoxic subvolumes among the AC patients, the percentage of positive tumor cells within hypoxic regions were statistically significantly lower in the NRCHT than in the R cohort across all the markers except for PD1. Conclusion: In this pilot study, we showed changes in the TME induced by NRCHT in both SCC and AC. These findings will be correlated with microscopic tumor extension measurements in a subsequent cohort of patients.